Sujuvuustutkimuksen käänteitä: Katsaus sujuvuustutkimuksen menetelmiin - Pekka Lintunen; Maarit Mutta; Pauliina Peltonen (AFinLA, 2022)
Fluency is a multifaceted concept used in language teaching and language learning research. Fluency is often approached as cognitive, utterance or perceived fluency. This review article focuses on Finnish fluency studies in which fluency has been examined with explicitly defined measures or criteria in a specific language skill. Our goal was to investigate what kinds of methods have been used and which subskills have been studied from the perspective of fluency. We also aimed to identify potential gaps in fluency research. According to our review, Finnish studies on L2 fluency have mostly focused on productive language skills (speaking and writing), while L1 fluency research has mostly focused on reading (dyslexia). Listening fluency has not been studied explicitly. The reviewed studies concerned various languages, populations and employed both quantitative and qualitative methods. We conclude that more research is needed on receptive skills, especially listening, multimodal fluency and fluency in new learning environments.